Improvements in petrol engine performance with ultrasonic fuel atomisation - Norster, E. R. (College of Aeronautics, 1966)
Initial studies of the effect of air-fuel mixture preparation on piston engine performance have been conducted on a four cylinder 1600 cc petrol engine using conventional carburation and ultrasonic fuel atomisation. The performance of the engine, under various conditions of operation, has been assessed on the basis of specific fuel consumption and brake mean effective pressure. Whereas only minor differences in performance were found under full power condition at part throttle running of the engine with ultrasonic fuel atomisation improvements in fuel consumption in excess of 10% were observed. These improvements appear to be the direct result of better mixture preparation. Indirect benefits of improved mixture preparation may be a reduction in exhaust smoke and hydrocarbon emission from the engine.